Estimating flood susceptibility of Bangladesh in the future year using machine learning - Alim, Sakib Bin; Lucky, Rakebun Islam; Ahmed, Aunindya Arif; Nahian, Prethu (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.